REEVALUAREA UNOR STRUCTURI CURRICULARE ALE FIZICII ÎN ORGANIZAREA CURRICULUMULUI OPŢIONAL - USM ADMIN (Moldova State University, 2009)
A review of some of curricular physics programs developed in the last fifty years may identify methods and strategies useful in optional curricula development by school and local community. It also may form the essence of education realized by school in the interest of, and for the community. Such an option could be a useful instrument of the developers of optional curriculum at school level, by the information and expertise it furnishes. It may be an open window to different philosophies of learning and teaching adapted to the local context. This work does a short presentation of two kind of integrated optionals the author has developed. The differences between the two optionals consist both in the way of doing and also in orientation, but both are student centered.